Value Of Ecocentrism in The Novel Supernova 4: Partikel Dewi Lestari - Mayandri, Ghaisyah Dwi; Supriyanto, Teguh; Setyaningsih, Nas Haryati (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Partikel is a novel about the struggles of Zarah and her friends on a nature saving mission. The purpose of this study is to analyze the ecological crisis, the impact of the ecological crisis, and the values of ecocentrism in the novel Partikel. The data collection method used is the first level semiotic reading method, namely by heuristic reading with a literary ecocritical research approach according to Garrad and Glotfelty. The results of the first study include the ecological crisis in forests and animals. Then the results of the second study were to find the impact of the ecological crisis that occurred in the Tanjung Puting Forest in Kalimantan, and the pollution of the Sekonyer river in Kalimantan. The ecocentrism values contained in the Partikel novel include saving forests as a form of responsibility towards nature, ecological ethics in the exploitation of natural resources, wildlife conservation park campaigns as a form of concern to nature and live in harmony with nature. The benefit of research is as an addition to knowledge to readers regarding the ecological crisis in nature and the impact that will be experienced by society.